2012
DOI: 10.1111/j.1526-4637.2012.01518.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Prescription Opioid-Related Death, Utah, 2008–2009

Abstract: Use of pain medication outside prescription bounds was a risk factor for death. However, decedents were more likely to have had chronic pain, and the majority of both groups had obtained pain medication by prescription. Other factors (e.g., smoking status) might also play important roles in prescription opioid-related death. Prescribers should screen chronic pain patients for risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 28 publications
7
46
0
Order By: Relevance
“…24 Regional and national studies have demonstrated PDM involving each drug class is associated with short-term and long-term consequences, including neuropsychological functioning, depressed mood, sleep problems and higher rates of SUD symptoms in adulthood. 2529 Clinicians can easily assess educational status when screening for PDM among young adults and make their patients aware of the growing evidence for adverse consequences associated with PDM.…”
Section: Discussionmentioning
confidence: 99%
“…24 Regional and national studies have demonstrated PDM involving each drug class is associated with short-term and long-term consequences, including neuropsychological functioning, depressed mood, sleep problems and higher rates of SUD symptoms in adulthood. 2529 Clinicians can easily assess educational status when screening for PDM among young adults and make their patients aware of the growing evidence for adverse consequences associated with PDM.…”
Section: Discussionmentioning
confidence: 99%
“…Because SPARCS does not collect prescription drug data, it is not possible to determine if patients were prescribed prescription opioids or other drugs at their ED visit. Similarly, other important characteristics cannot be accounted for such as, drugs taken, drug dosages, the setting in which drugs were taken or the mode of drug administration (e.g., oral or intravenous), factors associated with opioid adverse events, and overdose death [39,60,62,7173]. Fifth, there have been conflicting studies regarding the accuracy of drug overdose death certification and coding [7477].…”
Section: Discussionmentioning
confidence: 99%
“…Smoking-attributable mortality [67], overdose deaths from prescription drugs [68, 69], as well as alcohol-attributable mortality [70] have been clearly linked to the socioeconomic status.…”
Section: The Role Of Socioeconomic Statusmentioning
confidence: 99%